Coronary Embolism and Myocardial Infarction in a Transgender Male Undergoing Hormone Therapy: A Case Report and Review of the Literature - Sandesh Dinesh; Marcus Franz; Friedhelm Küthe (Case Reports in Cardiology)
Introduction. Due to the complex interaction between the underlying disease, psychosocial factors, and the high-dose hormonal therapy, transgender patients pose a therapeutic and diagnostic challenge, especially during emergencies. This case presents one such clinical dilemma using the example of a case of myocardial infarction. Case. A 35-year-old transgender male presented to our clinic with an acute inferior wall myocardial infarction. For the past 6 years, he was receiving high-dose testosterone therapy for the maintenance of hormone levels after female-to-male gender conversion. The emergency coronary angiography revealed a distal right coronary artery occlusion. Recanalization of the vessel was achieved by catheter-driven direct thrombectomy and subsequent intracardiac lysis. The appearance of the remaining coronary arteries bore no angiographic evidence of advanced coronary artery disease. We suspected a thromboembolic origin as the primary cause of the myocardial infarction. The presentation also fulfilled the proposed National Cerebral and Cardiovascular Center criteria for the clinical diagnosis of coronary embolism. In the diagnostic work-up, the most common causes of coronary embolism like atrial fibrillation, cardiomyopathies, endocarditis, and intracardiac tumors could be ruled out. The screening for hereditary thrombophilia was also negative. Likewise, the presence of a haemodynamically relevant right to left shunt could be excluded. In the end, the high-dose testosterone therapy seemed to be the most likely cause. Conclusion. Following major thromboembolic cardiovascular events, we believe that transgender males treated with high-dose testosterone therapy should receive oral anticoagulation, preferably with a DOAC, especially keeping in mind that the discontinuation of the hormone therapy is not always possible due to the various underlying psychosocial factors.